SAT0458 THE POLYMORPHISM ON FAT MASS AND OBESITY ASSOCIATED GENE (FTO) WAS ASSOCIATED WITH LOW BONE MASS IN JAPANESE COMMUNITY DWELLING POPULATION. (2nd June 2020) - Arima, K.; Tamai, M.; Nonaka, F.; Iwamoto, N.; Mizukami, S.; Nishimura, T.; Abe, Y.; Origuchi, T.; Aoyagi, K.
Abstract : Background: A polymorphism on FTO (OMIM 610966) was reported as a causal variant for obesity, plays a critical rule not only in amount of adipose tissue but also in function of mitochondrial thermogenesis1. Objectives: To examine the association of the genotype on a single nucleotide polymorphism on FTO with bone health. Methods: FTO rs1421085 polymorphism was genotyped in 1, 601 community-dwelling Japanese participants. This cross-sectional study was nested in Nagasaki Islands Study, which is a prospective cohort in Goto City, in islands of Japan. Participants were recruited at medical check-ups for community dwelling population. Bone mass of the calcaneus was evaluated with stiffness index calculated using a quantitative ultrasound measurement. Low bone mass was defined as a stiffness index less than 80 % of the young adult mean. Sera and peripheral blood mononuclear cells were obtained. The SNP of rs1421085 was genotyped using hydrolysis probe. The chi-squared test was used to determine whether the variants were in equilibrium in that population. Trend for the median of BMI among genotypes was assessed using the Jonckheere-Terpstra test. Potential associations between FTO polymorphism and overweight and between the polymorphism and low bone mass were evaluated using logistic regression. All analyses were carried out using SPSS 23. Results: Genotype and allele frequencies for the polymorphism were in Hardy-Weinberg equilibrium (minor allele frequency 0.16, p = 0.40) in 1, 601 community-dwelling persons (mean age was 68.5 years in men and 68.1 years in women). There were significant associations between the minor allele and higher median of BMI on dose dependent manner in men (p = 0.04 for trend in men and p = 0.10 for trend in women, respectively), and between the minor allele and overweight (>25 in BMI, OR 1.52, 95%CI 1.07 2.14, p=0.02 in men, OR 1.48, 95%CI 1.16 1.95, p=0.01 in women). Logistic regression analysis showed a significant protective association in men with carriers of minor allele against low bone mass after an adjustment for age and BMI (OR 0.63, 95%CI 0.44 0.90, p=0.01 in men, not significant in women). Conclusion: Our study indicated significant associations of the polymorphism on FTO with BMI and bone mass among community dwelling men. The polymorphism may play a rule in a part of bone health with higher BMI and other beneficial functions. References: [1]N Engl J Med. 2015; 373: 895-907 Disclosure of Interests: None declared